The Ho: living in a world of plenty of social cohesion and ritual friendship on the Chota Nagpur Plateau, India - Reichel, Eva 1948- (De Gruyter, 2020)
"The book is set in the anthropologically much-neglected multi-ethnic interior of Highland Middle India. It is the result of fieldwork done over a period of more than a decade among the Ho, an indigenous community of approximately one million people, who have shared cultural norms and the space of the hilly region of the Chota Nagpur Plateau with other aboriginal (adivasi) and artisan communities for ages. The book explores the structured tapestry of Ho people’s relations and interrelatedness within their culture-specific sociocosmic universe ensuring their social reproduction in the present and affording them the means for and the awareness of living in a world of plenty. This world of abundance – with the Ho as its conceptual centre – includes the Ho’s dead, their complex spirit world and supreme deity, and their tribal and nontribal fellow humans, and it manifests itself in manifold facets of their lives: socially, ritually, economically, and linguistically."--
Keywords: Ho; Weltbild; Gesellschaft; Indigenous peoples / India / Chota Nāgpur; Indigenous peoples; India / Chota Nāgpur